Understanding climate trends in Central America through practical problem-based learning. Issue 2 (3rd April 2021) - Sekhon, Natasha; Beach, Tim; Krause, Samantha; Eshleman, Sara
ABSTRACT: In our current period of escalating climate change, we urgently need to better understand the modern climate and climate drivers in understudied regions of the world. This article provides a succinct and current literature review of one such region: the Maya Lowlands. The region has a long history of study on human–climatic interaction but little regarding modern climate research. To spur the study and understanding of climate in this region, we present an applied exercise of climate drivers and data. First, the article will provide an update on the current knowledge of the modern climate drivers in the Maya Lowland regions. To provide breadth in the studies, we base our review on different climate time-scale variabilities. Second, we present results from a pilot exercise on applied climate trends exercised at an institute of higher education. Through practical problem-based learning, students investigate climate trends using climate data for the Maya Lowlands, and gain an insight into data management. The feedback gathered from the exercise helped formulate a revised edition to be used by instructors. Follow-up discussion questions and steps required to conduct the exercise are included. Through interdisciplinary techniques, the exercise aims for students to analyse critically the changing climate.